Point-of-Care Ultrasound in Pediatric Diagnostic Dilemmas: Two Atypical Presentations of Intussusception. Issue 1 (January 2019) - Sharma, Priya; Al-Sani, Faisal; Saini, Sidharth; Sao Pedro, Tais; Wong, Peter; Etoom, Yousef
Abstract : Abstract: Diagnostic dilemmas are ubiquitous in pediatric emergency medicine because of the varied and often insidious presentations of many pediatric conditions. Point-of-care ultrasound (POCUS) in emergency departments is being used for some of these diagnostic challenges and can often provide rapid and valuable information to supplement a physician's clinical assessment. Intussusception is a pediatric condition that may be challenging to recognize because of its subtle and varied presenting symptoms. An unrecognized or delayed diagnosis of intussusception can be catastrophic, with complications including bowel obstruction, bowel perforation, and death. Here we present two challenging cases of intussusception, one due to its atypical age of presentation and the other due to its unique symptoms. These cases demonstrate the benefits of point-of-care ultrasound for diagnostically challenging cases in the emergency department. Abstract : Supplemental digital content is available in the text.